2011
DOI: 10.1186/1471-2296-12-104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an audiovisual message for tetanus booster vaccination broadcast in the waiting room

Abstract: BackgroundGeneral practitioners (GPs) often lack time and resources to invest in health education; audiovisual messages broadcast in the waiting room may be a useful educational tool. This work was designed to assess the effect of a message inviting patients to ask for a tetanus booster vaccination.MethodsA quasi experimental study was conducted in a Belgian medical practice consisting of 6 GPs and 4 waiting rooms (total: 20,000 contacts/year). A tetanus booster vaccination audiovisual message was continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…This medium can increase the patient’s understanding of and satisfaction with their care, [19-22] and decrease their anxiety levels. Although videos can effectively improve knowledge about a complex topic, [20] or increase the participation in a prevention programme, [23] their use in waiting rooms is subject to technical constraints [24]. Information videos are more expensive to produce and broadcast in waiting rooms, which constitutes an obstacle to their development in a context of limited resources [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…This medium can increase the patient’s understanding of and satisfaction with their care, [19-22] and decrease their anxiety levels. Although videos can effectively improve knowledge about a complex topic, [20] or increase the participation in a prevention programme, [23] their use in waiting rooms is subject to technical constraints [24]. Information videos are more expensive to produce and broadcast in waiting rooms, which constitutes an obstacle to their development in a context of limited resources [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore unclear how meaningful the results of this intervention are on a broader scale. Due to the complexity of behaviour change (Michie et al, 2009;Michie et al, 2005), it may be argued that any degree of behaviour change, for example 0.79% of the study population (Eubelen et al, 2011), could be a positive outcome at population level. Consideration of the clinical significance of the costeffectiveness of improvements is warranted prior to implementation of future interventions Interventions that exclusively focus on a single domain, such as knowledge, often fail to achieve sustainable results in terms of behaviour change (Catania et al, 1990;Nutbeam, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted behaviours included preventive screening and vaccinations as well as behaviours such as smoking, dietary intake and physical activity. The studies reported improvements in participants' health related behaviours with a range of 0.79-44% of participants modifying behaviour as a result of the intervention (Cotter & Wilson, 1975;Eubelen et al, 2011;Gliori et al, 2006;Goldschmidt & Goodrich, 2004;Jackson et al, 2010;Janda et al, 2002;Krishna et al, 2003;Leijon et al, 2011;Rose et al, 2010;Yancey et al, 1995). Although favourable improvements are reported, the clinical significance of the improvement was not often considered (Cotter & Wilson, 1975;Giordano et al, 2013;Mead et al, 1995).…”
Section: Health Related Behavioursmentioning
confidence: 99%
“…Established in 1944, the World Bank is a partner with the GAVI Alliance and is a vital source of financial and audiovisual messages in clinic waiting rooms showing educational material increases awareness (Eubelen et al, 2011). Short video clips with children portraying pertussis in the clinic waiting rooms with a message regarding the vaccination requirement will have an impact.…”
Section: Improving Vaccination Ratesmentioning
confidence: 99%